The The Use of Smartphone to Improve Pronunciation Ability of 6th Grade Students in Sikka Regency - Fitriah, Fitriah; Pugar Alam, Satria; Labira, Darmawan (Udayana Journal of Social Sciences and Humanities, 2024)
The objectives of this research were to prove that using smartphone can increase pronunciation ability of 6th grade at SDN Ngolo, Sikka regency. This research applied pre-experimental research using one group pre-test and post-test. The researchers used all students from 6 th grade as an object which consisted of 15 students. The result showed that the use of smartphone was able to improve pronunciation ability. It is proven by the hypothesis testing showed that the value of t-test (7.22) was greater than t-table (2.14479). The percentage of improvement was 31.4%